2020
DOI: 10.1101/2020.03.01.972026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

JNK pathway restricts DENV, ZIKV and CHIKV infection by activating complement and apoptosis in mosquito salivary glands

Abstract: 150 words) 23 Arbovirus infection of Aedes aegypti salivary glands (SGs) determines transmission. 24 However, there is a dearth of knowledge on SG immunity. Here, we characterized SG 25 immune response to dengue, Zika and chikungunya viruses using high-throughput 26 transcriptomics. The three viruses regulate components of Toll, IMD and JNK pathways. 27 However, silencing of Toll and IMD components showed variable effects on SG infection by 28 each virus. In contrast, regulation of JNK pathway produce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Varied with the regulatory pathway involved, arbovirus species and vector tissue, apoptosis may have contrasting effects on arbovirus loading within insect vectors. The antiviral JNK pathway-activated apoptosis restricts the arboviruses Dengue, Zika and Chikungunya in salivary gland of Aedes aegypti , while current study shows that MAPK-dependent activation of apoptosis promoted TYLCV loading in MED whitefly (Chowdhury et al, 2020). Likewise, apoptosis occurred in midgut of Ae.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Varied with the regulatory pathway involved, arbovirus species and vector tissue, apoptosis may have contrasting effects on arbovirus loading within insect vectors. The antiviral JNK pathway-activated apoptosis restricts the arboviruses Dengue, Zika and Chikungunya in salivary gland of Aedes aegypti , while current study shows that MAPK-dependent activation of apoptosis promoted TYLCV loading in MED whitefly (Chowdhury et al, 2020). Likewise, apoptosis occurred in midgut of Ae.…”
Section: Discussionmentioning
confidence: 57%
“…The copyright holder for this preprint this version posted January 20, 2021. ; https://doi.org/10.1101/2021.01.19.427364 doi: bioRxiv preprint restricts the arboviruses Dengue, Zika and Chikungunya in salivary gland of Aedes aegypti, while current study shows that MAPK-dependent activation of apoptosis promoted TYLCV loading in MED whitefly (Chowdhury et al, 2020). Likewise, apoptosis occurred in midgut of Ae.…”
Section: Regulation Of Pebp-mapk Signaling Cascade On Apoptosis Activationmentioning
confidence: 59%
“…Of the 44 transcription factors, 3 had previously been linked with insecticide resistance in Anopheles mosquitoes and just 11 had been previously studied in mosquito species in any context (Amenya et al, 2010;Chen et al, 2017;Chowdhury et al, 2020;Fu et al, 2020;Ingham et al, 2018Ingham et al, , 2017Luna et al, 2006;Maliti et al, 2016;Ruiz et al, 2019;Wang et al, 2017;Wülbeck and Simpson, 2002). All but 4 of these transcription factors have a welldefined role in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these transcription factors have known roles in stress response in Drosophila (Table 1); however, only Maf-S, Met and Dm have previously been linked with insecticide response in mosquitoes (Ingham et al, 2018(Ingham et al, , 2017. Of the transcription factors selected for analysis the following have been studied in mosquitoes: p53 has been shown to respond to arboviral infection (Chen et al, 2017); Rbsn-5 has been shown to be involved in egg shell formation (Amenya et al, 2010); l(1)sc is linked with sensory tissue development (Wülbeck and Simpson, 2002); kayak is involved in salivary gland response to arboviral infection through JNK pathway activation (Chowdhury et al, 2020); Hnf4 is linked to ecdysone and Met mediated lipid metabolism (Wang et al, 2017); Cyc controls the circadian ryhthm (Maliti et al, 2016); REL1 and REL2 are involved in immune response (Luna et al, 2006); Kr-h1 is essential for egg development (Fu et al, 2020) and Pan is linked with chromatin changes upon Plasmodium infection (Ruiz et al, 2019). et al (Rämet et al, 2002; Miotto et al 2006(Miotto et al, 2006 RNA-related Processes…”
Section: Identification Of Transcription Factors Involved In Insecticmentioning
confidence: 99%
“…Infection of the salivary glands also changes the content of saliva, affecting blood acquisition and skin infection 5 . DENV ZIKV and CHIKV infections activate the c-jun N terminal kinase (JNK) pathway, activating complement and apoptotic effectors, resulting in a broad antiviral response 6 . The ZIKV pandemic was a "perfect storm" in which a novel American subclade arose from the virus's Asian origin and was introduced into a uniformly susceptible population that had never been exposed to ZIKV before 7 .…”
mentioning
confidence: 99%